THE SEMIDIURNAL M2 TIDE IN THE SOUTHEAST ASIAN WATERS - Kastoro, - (Marine Research in Indonesia, 1987)
The semidiurnal tides of the Pacific and Indian Oceans penetrate deeply into the Southeast Asian waters. The tides of the Pacific Ocean govern the whole of the China Sea, the Philippines waters and the Sulawesi Sea while the tides of the Indian Ocean govern the Timor Sea, the Banda Sea, the Andaman Sea and the Malacca Strait. The Maluku Sea, the Makassar Strait and the Java Sea are the boundary region between tides from the Indian and Pacific Oceans. In the Java Sea the semidiurnal tide is produced mainly by the tide from the Indian Ocean. At the boundary region, the amplitudes are generally very small. As an example of a boundary region, the tides of the Sunda Strait are considered in some detail. An analytical solution of two overlapping standing waves, one wave resulting from open mouth reflection of a wave incident from the Indian Ocean and the other standing wave from open mouth reflection of a wave incident from the Java Sea, adequately describe the M2 tide in the Sunda Strait.